Emerging consumer preference for wine attributes in a European transition country: The case of Kosovo - Edvin Zhllima; Drini Imami; Njazi Bytyqi; Maurizio Canavari; Elvina Merkaj; Catherine Chan-Halbrendt (Wine Economics and Policy, 2020)
This study analyzes consumer preferences for wine in Prishtina, Kosovo - a transition country in the Balkans, which is making efforts to withstand to the competition pressure from the traditional neighboring wine producing countries. With the changes in life style and consumer behavior, and incomes rising rapidly since the last conflict, it is imperative to survey the changing demand for producers to compete in the domestic markets. Conjoint Choice Experiments were used to evaluate wine consumer preferences based on wine type (white vs. red), origin (domestic vs. imported), taste (sweet vs. dry) and price. Four distinct classes of consumers were identified. The top two important attributes in the choice of wine are the type and origin but preferences vary across groups - type of wine and origin appear far more important when compared to price, especially for the richest identified segment, whose consumers prefer more expensive wines.
Keywords: 330; consumer preferences; wine; Conjoint Choice Experiment; latent class choice model; Kosovo